2017
DOI: 10.1007/s12098-017-2562-3
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella typhimurium Meningitis in an Infant Presenting with Recurrent Meningitis

Abstract: Salmonella typhimurium meningitis in infancy is very uncommon and does not respond to usual duration of empirical antibiotic therapy. A 5-mo-old infant presented with clinical picture of acute pyogenic meningitis and was treated with empirical antibiotic therapy for 14 d. But, 2 wk after the discharge, the child presented again with similar complaints. CSF culture had grown Salmonella typhimurium following which dual antibiotic therapy was given for 6 wk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…However a study involving five Asian countries demonstrated Salmonella typhi and para-typhi to be the most common organism being isolated [12]. Salmonella species both typhi and non-typhi usually spread by faecooral contamination [1]. Therefore the presence of invasive Salmonella non-typhi disease in a region where S. typhi strains are endemic was a cause for concern as this patient also had no other risk factors and was also on exclusive breast feeding.…”
Section: Salmonellamentioning
confidence: 89%
See 4 more Smart Citations
“…However a study involving five Asian countries demonstrated Salmonella typhi and para-typhi to be the most common organism being isolated [12]. Salmonella species both typhi and non-typhi usually spread by faecooral contamination [1]. Therefore the presence of invasive Salmonella non-typhi disease in a region where S. typhi strains are endemic was a cause for concern as this patient also had no other risk factors and was also on exclusive breast feeding.…”
Section: Salmonellamentioning
confidence: 89%
“…Acute bacterial meningitis, a medical emergency requires prompt treatment and early initiation of intravenous antibiotic therapy is required even before the etiology is known [1,2]. Only few case reports have been reported in literature of Salmonella typhimurium causing meningitis in immuno-competent infants especially from tropical countries [1,2,6]. A recent case report from India reported a case of acute pyogenic meningitis from Salmonella typhimurium leading to subdural empyema and brain abscess [6].…”
Section: Salmonellamentioning
confidence: 99%
See 3 more Smart Citations